Self-Knowledge and the Self. - Jopling, David A. (Routledge, 2000)
In this clear and reasoned discussion of self- knowledge and the self, the author asks whether it is possible truly to know ourselves. He looks at issues of great importance in moral psychology, epistemology, literary criticism.